Correction to: Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)
The article Microbial Exchange via Fomites and Implications for Human Health, written by Brent Stephens, Parham Azimi, Megan S. Thoemmes, Mohammad Heidarinejad, Joseph G. Allen, and Jack A. Gilbert, was originally published electronically on the publisher’s internet portal